Handling of General Election Crimes in the Framework of Realizing Democratic and Responsible General Elections - Muhammad Sarkani; Ridwan; Mada Apriandi; Henny Yuningsih (Khazanah Sosial, 2025)
This study aims to evaluate the effectiveness of the Election Supervisory Body (Bawaslu) in handling election crimes, focusing on supervision mechanisms, policy implementation, and law enforcement outcomes. A descriptive qualitative method was used, with data collected through literature reviews on election regulations, Bawaslu reports, and relevant previous studies. The analysis assessed Bawaslu’s performance based on supervision quality, coordination with the Integrated Law Enforcement Center (Gakkumdu), law enforcement effectiveness, and obstacles encountered. The findings indicate that Bawaslu’s effectiveness relies on clear reporting procedures, responsiveness in handling reports, and investigative objectivity. Coordination with Gakkumdu plays a crucial role in ensuring transparent and efficient law enforcement, contributing to a decrease in election violations. However, challenges such as limited resources and weak regulations hinder optimal performance. This study highlights the need for capacity building, regulatory improvements, and stronger institutional synergy to enhance election crime handling.